Quarterly review - Federal Reserve Bank of Minneapolis (MInneapolis Federal Reserve Bank of Minneapolis, Research Department, 1999)
It Primarly represents economic research aimed at improving policymaking by the Federal Reserve System and other governmental authorities.
FRB WP: Beginning with the February 2012 issue, the <em style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-stretch: inherit; line-height: inherit; font-family: Arial, Helvetica, sans-serif; vertical-align: baseline; color: rgb(63, 88, 114);">QR became a fully electronic, online-only journal, which is downloadable in PDF format. Only one issue from 2011 is available at the library (Feb 2011)
Keywords: Banks and Banking; ECONOMIC HISTORY; ECONOMIC CONDITIONS; FEDERAL RESERVE BANKS; USA; PERIODICALS